Identifying spatial variation in the values of urban green at the city level: A case study in Thessaloniki, Greece - Giannakidou, Antonia; Latinopoulos, Dionysis (TeMA - Journal of Land Use, Mobility and Environment, 2023)
Analyzing the benefits/values of urban green spaces (UGS) to local citizens is necessary in order to make these areas more visible, as well as to support future planning decisions related to the development of new green infrastructure in the urban environment. This paper aims to examine the values associated with the UGS in the city of Thessaloniki, Greece, by using a Hedonic Pricing Method, which examines the effect of urban green areas and amenities on housing prices. Furthermore, the study attempts to examine if the proximity to green spaces has a fixed/homogenous effect on residential property values across the city. A global regression analysis was first applied to explore which structural, locational and green/environmental characteristics are likely to have a statistically significant effect on housing prices. Then, a semi-parametric geographically weighted regression analysis, was applied to identify how the implicit prices of the environmental/green attributes vary within the city. The study revealed that the values of several environmental attributes vary significantly spatially, having in most cases a positive influence on home sale prices. These findings reveal that when making planning decisions about urban green spaces, it is necessary to consider the heterogeneity of citizens’ preferences, facilitating thus a more targeted planning for new green infrastructures.